The Impact Of Education Level, Accountancy Comprehension, And Readiness Level Of Micro, Small, And Medium Enterprises (MSMES) In Central Jakarta On The Preparation Of Financial Reports Based On SAK EMKM - Wadastika Nurohmah (Publikasi Indonesia, 2023)
This research analyzes the relationship between education level, accounting understanding, and readiness level of micro, small, and medium enterprises (MSMEs) in Central Jakarta in the activity of preparing financial reports according to SAK EMKM. The research is based on the importance of preparing financial reports to support MSMEs and enhance access to capital and markets. However, many MSMEs face difficulties in preparing financial reports, especially due to the low education level, accounting knowledge, and readiness to adopt SAK EMKM. The research employed a survey method, with 260 respondents from MSMEs in Central Jakarta. Data analysis was conducted using multiple regression. The results show that education level and accounting abilities have a significant influence on the ability to prepare financial reports according to SAK EMKM. Furthermore, readiness level does not have a significant influence on the skills of MSMEs in preparing financial reports. Therefore, MSMEs need to improve their education and accounting understanding to effectively prepare financial reports in accordance with SAK EMKM.